THE EFFECT OF APPLYING THE STRATEGY OF EDUCATIONAL SCIENTIFIC PILLARS ON THE LEVEL OF PERFORMANCE OF SOME HANDBALL SKILLS AMONG PLAYERS MISAN UNIVERSITY - Abbas Taha Hussein; Munadhil Adil Kasim (American Journals Publishing, 2023)
The aim of the research is to identify the effectiveness of the educational scientific pillars on the level of performance of some handball skills among players Misan University. To achieve the research objectives, the study employed the experimental method and utilised a quasi-experimental design involving two comparable groups. The first group, referred to as the control group, received traditional instruction, while the second group, referred to as the experimental group, was taught using the educational pillars strategy. The research sample comprised 30 students from the second phase. These students were intentionally selected to ensure equivalence, considering factors such as chronological age, height, and weight and proficiency. They were then evenly divided into two groups: an experimental group and a control group. The teacher's handbook included a representation of research tools for the implementation of the educational pillar's strategy. These tools consisted of an achievement test to assess the level of performance in handball skills among players, as well as a skills test. The experiment was implemented during the initial semester of the academic year (2021/2022) by the researchers. The experimental group was instructed using the educational pillars strategy, whereas the control group followed the conventional method of studying. The experimental and control research groups underwent the application of the scrolling and receiving, dribbling, and shooting from stability skill test. Subsequently, the data required for statistical analysis and access to results were obtained. The findings indicated that there were statistically significant disparities in the average scores of the experimental group and control group regarding the proficiency level of certain handball skills among the players. Significant statistical differences were observed in the mean scores of the two groups in relation to the skills of scrolling and receiving, dribbling, and shooting from stability skill. The magnitude of these differences was determined by assessing the effectiveness of the educational pillar's strategy. The findings indicate that the implementation of the educational pillar's strategy has a substantial mpact on the performance level of certain handball skills among players of Misan University.
Keywords: Applying, Strategy, Scientific, Pillars, Handball